A Flexible Electrochemiluminescence Sensor Equipped With Vertically Ordered Mesoporous Silica Nanochannel Film for Sensitive Detection of Clindamycin - Wei, Xinjie; Luo, Xuan; Xu, Shuai; Xi, Fengna; Zhao, Tingting (Frontiers in Chemistry, 2022)
Fast, convenient, and highly sensitive detection of antibiotic is essential to avoid its overuse and the possible harm. Owing to enrichment effect and anti-fouling ability of ultrasmall nanochannels, vertically-ordered mesoporous silica-nanochannel film has great potential in the development of facile electrochemiluminescence (ECL) sensor for direct and sensitive analysis of antibiotics in complex samples. In this work, we demonstrated a flexible ECL sensor based on cost-effective electrode covered with VMSF for sensitive detection of clindamycin. Polyethylene terephthalate coated with indium tin oxide (PET-ITO) is applied as the flexible electrode to grow VMSF through electrochemically assisted self-assembly (EASA) method. The negatively charged VMSF nanochannels exhibit significant enrichment towards the commonly used cationic ECL luminophores, tris(2,2-bipyridyl) dichlororuthenium (II) (Ru(bpy)32+). Using the enhanced ECL of Ru(bpy)32+ by clindamycin, the developed VMSF/PET-ITO sensor can sensitively detect clindamycin ranged from 10 nmol/L to 70 mol/L with a limit of detection (LOD) of 4 nmol/L. Owing to the nanoscale thickness of VMSF and the high coupling stability with the electrode substrate, the developed flexible VMSF/PET-ITO sensor exhibits high signal stability during the continuous bending process. Considering high anti-fouling characteristic of VMSF, direct analysis of clindamycin in real biological sample, human serum, is realized.